2022
DOI: 10.1002/aenm.202200959
|View full text |Cite
|
Sign up to set email alerts
|

High‐Performance Rechargeable Aluminum‐Ion Batteries Enabled by Composite FeF3 @ Expanded Graphite Cathode and Carbon Nanotube‐Modified Separator

Abstract: Rechargeable aluminum ion batteries (AIBs) are one of the most promising battery technologies for future large‐scale energy storage due to their high theoretical volumetric capacity, low‐cost, and high safety. However, the low capacity of the intercalation‐type cathode materials reduces the competitiveness of AIBs in practical applications. Herein, a conversion‐type FeF3‐expanded graphite (EG) composite is synthesized as a novel cathode material for AIBs with good conductivity and cycle stability. Combined wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…Although multi-valent metals (i.e. Zn, Al) have achieved much longer cycle life than alkali metals [35,36], it lacks a good understanding on their exact working mechanisms during the charge/discharge process and why they behave differently from alkali metals.…”
Section: Statusmentioning
confidence: 99%
“…Although multi-valent metals (i.e. Zn, Al) have achieved much longer cycle life than alkali metals [35,36], it lacks a good understanding on their exact working mechanisms during the charge/discharge process and why they behave differently from alkali metals.…”
Section: Statusmentioning
confidence: 99%
“…Various recent studies have reported the application of conductive matrix materials in FeF x cathodes. Wherein, carbon‐based FeF x composites have been the preferred method to optimize the electrochemical properties of FeF x cathodes [87,88] . Carbon materials have tunable structures and excellent mechanical stability, providing sufficient active sites and promoting interfacial ion diffusion.…”
Section: Strategies Of Improved Fefx Performancementioning
confidence: 99%
“…Wherein, carbonbased FeF x composites have been the preferred method to optimize the electrochemical properties of FeF x cathodes. [87,88] Carbon materials have tunable structures and excellent mechanical stability, providing sufficient active sites and promoting interfacial ion diffusion. It plays a crucial role in the electron/ion transport and structural stability of FeF x cathodes.…”
Section: Conductive Matrixmentioning
confidence: 99%
“…Typically, liquid-phase synthesis, including chemical precipitation, [60] hydrothermal, [61] solvothermal, [62,63] sol-gel, [64] and thermal decomposition methods [65] based on different fluorine sources, (hydrogen fluoride (HF) solution, [66] NH 4 F, [67] NH 4 HF 2 , [68,69] metal hexafluorosilicate, [70] F-containing ionic liquids (ILs), [71] etc.) has been utilized to prepare nanoparticle MFs, [72] metal oxyfluorides, [73] mixed metal difluorides, [74] and MF-carbon composites.…”
Section: Liquid-phase Synthesismentioning
confidence: 99%